Binding Nanosized Cobalt Chalcogenides in B, N‐Codoped Graphene for Enhanced Sodium Storage. Issue 4 (25th July 2018) - Cheng, Xiaolong; Li, Dongjun; Liu, Fanfan; Xu, Rui; Yu, Yan
Abstract: A general process is developed to prepare binding nanosized cobalt chalcogenides in B, N‐codoped graphene (CoSe2 /BNG and CoS2 /BNG). When used as anodes for sodium‐ion batteries, the CoSe2 /BNG and CoS2 /BNG deliver excellent sodium‐storage performance. The CoSe2 /BNG displays a reversible capacity of 270 mAh g −1 after 2000 cycles at a current density of 1 A g −1 . Even at 20 A g −1, it can still give a capacity of 187 mAh g −1 . Moreover, the CoS2 /BNG shows 387 mAh g −1 at 10 A g −1, demonstrating its superior high rate performance. The enhanced sodium‐storage properties of the CoSe2 /BNG and CoS2 /BNG nanocomposites may be attributed to the high conductive graphene network, enhanced sodium storage of B, N‐codoping in graphene, and the small CoSe2 and CoS2 nanocrystallites that shorten the electronic and ionic diffusion length throughout the electrode. Abstract : Nanosized cobalt chalcogenides anchored in B, N‐codoped graphene (CoSe2 /BNG and CoS2 /BNG) are prepared by a newly developed general process. When used as anodes for sodium‐ion batteries, the CoSe2 /BNG and CoS2 /BNG deliver superior cycling stability and excellent rate performance.